The Correlation Between Linguistic Intelligence and Reading Habit of English Study Program Students of Riau University - Apriani. E, Nabilla; Eliwarti, Eliwarti; Masyhur, Masyhur (TELL - US JOURNAL, 2025)
The aim of this study was to find out whether there was significantly correlation or not between linguistic intelligence and reading habit. Thirty-four students as sample by using random cluster sampling technique. The method of this study was correlational research. It was found that the outcome of this analysis is Sig. (2-tailed) value is 0.944, and it is greater than 0.05. It can be concluded that there was no significant correlation between linguistic intelligence and reading habit.